Lack of VEGFA/KDR signaling in conventional renal cell carcinoma explains the low efficacy of target therapy and frequent adverse events - Peterfi, Lehel; Yusenko, Maria V.; Kovacs, Gyula; Beothe, Tamas (International journal of molecular sciences, 2024)
It is acknowledged that conventional renal cell carcinoma (cRCC), which makes up 85% of renal malignancies, is a highly vascular tumor. Humanized monoclonal antibodies were developed to inhibit tumor neo-angiogenesis, which is driven by VEGFA/KDR signaling. The results largely met our expectations, and in several cases, adverse events occurred. Our study aimed to analyze the expression of VEGFA and its receptor KDR by immunohistochemistry in tissue multi-array containing 811 cRCC and find a correlation between VEGFA/KDR signaling and new vessel formation. None of the 811 cRCC displayed VEGFA-positive immunostaining. However, each glomerulus in normal kidney showed VEGFA-positive endothelial cells. KDR expression in endothelial meshwork was found in only 9% of cRCC, whereas 2% of the cRCC displayed positive KDR reaction in the cytoplasm of tumor cells. Our results disclose the involvement of VEGFA/KDR signaling in the neo-vascularization of cRCC and explain the frequent resistance to drugs targeting the VEGFA/KDR signaling and the high frequency of adverse events.